Effect Of Different Type Of Isocyanates On The Properties Of Shape Memory Polyurethane Elastomer Based On Palm Kernel Oil Polyol - Chai, Shir Ying (Universiti Sains Malaysia, 2018)
The performance of the shape memory polyurethane (SMPU) elastomers depends on chemical composition, chemical structure, the extent of hydrogen bonding and microphase-separated structure. This paper reports the study of palm kernel oil (PKO) polyol based SMPU. In this study, the molar ratio and types of isocyanate were used as manipulated variables. The SMPUs were synthesized via a two-step bulk polymerization method using polycaprolactone diol and PKO as soft segment, 1,6-hexamethylene diisocyanate/ 4,4 methylene-bis(cyclohexyl isocyanate)/ isophorone diisocyanate and 1,4-butanediol as the hard segment with dibutyltin dilaurate as the catalyst. Several characterizations such as Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetric, Thermal Gravimetric Analysis, X-ray Diffraction and tensile test were carried out to investigate the structural, thermal and mechanical properties of SMPUs. Shape memory test is performed to investigate the shape memory behaviour of SMPUs. It was found that the crystallinity of SMPU soft segments and shape fixity of SMPUs decreases with increasing of the hard segment content. In overall, IPDI 154 sample demonstrate higher modulus value and shape fixity properties as compared to HDI 154 and HMDI 143 samples while HMDI+IPDI 165 sample shows better shape fixity, higher modulus value and tensile strength ascompared to IPDI 165 sample.